2018
DOI: 10.1038/s41559-018-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for close-range hunting by last interglacial Neanderthals

Abstract: Animal resources have been part of hominin diets since around 2.5 million years ago, with sharp-edged stone tools facilitating access to carcasses. How exactly hominins acquired animal prey and how hunting strategies varied through time and space is far from clear. The oldest possible hunting weapons known from the archaeological record are 300,000 to 400,000-year-old sharpened wooden staves. These may have been used as throwing and/or close-range thrusting spears, but actual data on how such objects were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 23 publications
0
63
0
Order By: Relevance
“…In many experiments, apes were raised in human environment and exposed to recursive language from infancy. These animals commonly learn hundreds to thousands of words but never acquired PFS (tested linguistically and nonverbally) (Gardner et al 1989, Patterson and Linden 1981, Tomasello 2010, consistent with some neurobiological barrier, possibly, a short critical period, preventing them from acquiring PFS. Additionally, genetic and imaging studies showed that ape's PFC develops significantly faster than PFC in modern humans.…”
Section: The Genetic Triggermentioning
confidence: 57%
See 2 more Smart Citations
“…In many experiments, apes were raised in human environment and exposed to recursive language from infancy. These animals commonly learn hundreds to thousands of words but never acquired PFS (tested linguistically and nonverbally) (Gardner et al 1989, Patterson and Linden 1981, Tomasello 2010, consistent with some neurobiological barrier, possibly, a short critical period, preventing them from acquiring PFS. Additionally, genetic and imaging studies showed that ape's PFC develops significantly faster than PFC in modern humans.…”
Section: The Genetic Triggermentioning
confidence: 57%
“…However, whether or not these sites constitute actual burial sites is hotly disputed. Their preservation could well be explained by natural depositions (Gargett et al 1989). Even if those burials were made deliberately, the goal may have been to simply toss the bodies away in order to discourage hyena intrusion into the caves (Tattersall 1999).…”
Section: Adorned Burials and Religious Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern humans, on the other hand, could have chased a mammoth into a pitfall trap where immobilized weakened animal could have been easily killed. Comparison of archeological remains between early modern hominines and Neanderthals is therefore expected to show disproportionally larger number of broken bones in Neanderthals that must have resulted from this close contacts with large animals 66,160,161 .…”
Section: Neanderthal Speech Culture and Hunting Stylesmentioning
confidence: 99%
“…300,000 to 40,000 years ago. Whilst debates about their capability and capacity for sophisticated behaviours are ongoing, current archaeological evidence suggests that these groups were successful hunters of various species of large to medium sized animals (Gaudzinski 1995;Marean and Kim 1998;Gaudzinski and Roebroeks 2000;Steele 2002;Villa and Lenoir 2009;Discamps et al 2011;Morin 2012;Rendu et al 2012;Villa and Roebroeks 2014;Morin et al 2015;Smith 2015;Gaudzinski-Windheuser et al 2018). Such behaviour has been identified within both glacial and interglacial phases, and though there are subtle variations in terms of the species, the overall pattern remains consistent (Gaudzinski-Windheuser et al 2014a, b;Sinet-Mathiot et al 2019).…”
Section: Introductionmentioning
confidence: 99%